Perancangan Pengaduan Informasi Haji Dan Umrah Berbasis Web Menggunakan Metode Prototype - Muhammad Mushleh; Sri Rahayu (Jurnal Pengembangan Teknologi Informasi dan Komunikasi (JUPTIK), 2025)
The pilgrimage of Hajj and Umrah is a significant event in the lives of Muslims. The quality of service during this spiritual journey has a significant impact on the pilgrims' experience. Therefore, this research aims to design a web-based information system that facilitates complaints and reporting related to Hajj and Umrah services. The method used to design this system is Prototyping, allowing for gradual development and meeting user needs. The system will include features such as online complaint forms, complaint tracking, and interactive feedback mechanisms. The research aims to enhance the effectiveness and transparency of Hajj and Umrah claims and facilitate pilgrims in reporting their experiences. This will make it easier for users and administrators to engage in complaint activities regarding Hajj and Umrah information.